2016
DOI: 10.3389/fpsyg.2015.01960
|View full text |Cite
|
Sign up to set email alerts
|

Collective Efficacy in Sports and Physical Activities: Perceived Emotional Synchrony and Shared Flow

Abstract: This cross-sectional study analyzes the relationship between collective efficacy and two psychosocial processes involved in collective sport-physical activities. It argues that in-group identification and fusion with the group will affect collective efficacy (CE). A sample of 276 university students answered different scales regarding their participation in collective physical and sport activities. Multiple-mediation analyses showed that shared flow and perceived emotional synchrony mediate the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
1
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 48 publications
5
53
1
12
Order By: Relevance
“…The fact that these gatherings might constitute a fundamental human need is not the subject of this paper. Nevertheless, this study, like other ones (e.g., Carnes & Lickel, ; Rennung & Görtiz, ; Van Kleef & Fischer, ; Zumeta, Oriol, et al, ) suggests that such gatherings have a significant set of positive effects at both the individual and social levels. Knowledge of the potential of these gatherings and of the process underlying their virtuous effects therefore seems to constitute a significant lever for policy makers wishing to influence the sense of social integration and well‐being of their citizens.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The fact that these gatherings might constitute a fundamental human need is not the subject of this paper. Nevertheless, this study, like other ones (e.g., Carnes & Lickel, ; Rennung & Görtiz, ; Van Kleef & Fischer, ; Zumeta, Oriol, et al, ) suggests that such gatherings have a significant set of positive effects at both the individual and social levels. Knowledge of the potential of these gatherings and of the process underlying their virtuous effects therefore seems to constitute a significant lever for policy makers wishing to influence the sense of social integration and well‐being of their citizens.…”
Section: Discussionsupporting
confidence: 53%
“…In summary, studies on synchronization, be it during collective gatherings or using interpersonal experimental settings, point to the positive effect of synchronization on social integration (i.e., feeling of fusion with the group, ease of social interaction, mutual attraction, liking, closeness, collective identity), empowerment (i.e., self‐esteem, personal and collective effectiveness, openness to others and to experience), and adherence to shared beliefs (i.e., concerns evoked by the organization of a rally). Since the publication of Páez et al’s research (), there have been numerous other studies that have further shown the relevance of the neo‐Durkheimian model of collective processes in the study of collective gatherings (see e.g., Carnes & Lickel, ; Pelletier, ; Rennung & Görtiz, ; Van Kleef & Fischer, ; Wlodarczyk et al, ; Zumeta, Basabe, Wlodarczyk, Bobowik, & Páez, ; Zumeta, Oriol, Telletxea, Amutio, & Basabe, ). The body of knowledge about the effects of collective gatherings is rapidly growing and Durkheim's seminal ideas are gaining increasing empirical support.…”
Section: Introductionmentioning
confidence: 99%
“…In these situations, participants transcend their ego and get involved in a more complex action system that activates collective emotions (Csíkszentmihályi, 1990). In this same line, there is an in-creasing interest in the study of flow experiences from a collective perspective (Delle Fave, Massimini, & Bassi, 2013;Salanova, Rodríguez-Sánchez, Schaufeli, & Cifre, 2014;Zumeta, Oriol, Telletxea, Amutio, & Basabe, 2016). Shared emotional and behavioral processes are an important and exciting area of research in psychology and social sciences in general, where classic ideas like Durkheim's (1912) collective effervescence and emotional communion are examined with advanced research tools and more sophisticated macro psychological approaches (see von Scheve & Salmela, 2014 for a review of the collective emotions).…”
Section: Shared Flow and Positive Collective Gatheringsmentioning
confidence: 99%
“…The scale measuring shared flow originally derived from the Spanish version of Jackson and Marsh's Dispositional Flow Scale (1996) Zumeta et al 2013, was applied by Páez et al, 2015 andZumeta et al, 2016. The scale comprises 27 items distributed across nine dimensions: (1) Balance between challenge and skill; (2) Clear proximal goals; (3) Unambiguous and direct feedback; (4) Action-awareness merging; (5) Focused concentration on the current activity; (6) Sense of control over one's actions; (7) Loss of self-consciousness; (8) Loss of time awareness or time acceleration; (9) Autotelic experience.…”
Section: Measurement During the Event (T2)mentioning
confidence: 99%
“…The similarity of the structures of person and others will encounter the same feelings that they go through in their actual experiences. According to Zumeta, Oriol, Telletxea, Amutio, and Basabe (2016), in an experience where there is a shared emotion, it yields a relational involvement, achieves well-being, intensifies social integration, and builds an identity fusion. When a person and others meet through meaningful experience, it further strengthens their positive beliefs, social cohesion, interaction, and communication (Kimura & Daibo, 2006;Paez, Rime, Basabe, Wlodarczyk, & Zumeta, 2015).…”
Section: Antecedents: Triadic Experiences Of Person (I) -Other (You) -Wementioning
confidence: 99%